The Effect of Dates Palm (Phoenix Dactylifera) on Uterus Involution among Mother with Postpartum - Elv Feedia Mona Saragih; Suryati Kumorowulan; Diyah Fatmasari (Alta Dharma Publisher, 2020)
The absence of uterine contractions after labor caused problems during the postpartum period, especially in the process of uterine involution. Date palm fruit is a non-pharmacological therapy that contains oxytocin, which is good for postpartum mothers' consumption to maintain uterine contractions so that the involution process can run normally. The study aimed to examine the effect of date palm fruit consumption on uterine involution in postpartum mothers. A quasi-experimental study, pre and posttest with the equivalent control group. We involved 32 respondents and divided into experimental group (n = 16) and control group (n = 16). The results showed that the uterine revolution was faster in the intervention group after receiving the dates palm fruit (Phoenix dactylifera) compared to the control group. This study proves that there is an influence of consumption of dates on uterine involution in postpartum mothers. Further research needs to investigate the effect of the palm fruit on other variables related to uterus involution and expected to measure biomarkers such as prolactin